Forest microclimate dynamics drive plant responses to warming - Zellweger, Florian; De Frenne, Pieter; Lenoir, Jonathan; Vangansbeke, Pieter; Verheyen, Kris; Bernhardt-Römermann, Markus; Baeten, Lander; Hédl, Radim; Berki, Imre; Brunet, Jörg; Van Calster, Hans; Chudomelová, Markéta; et al. (Science (New York, N.Y.), 2020)
Climate warming is causing a shift in biological communities in favor of warm-affinity species (i.e., thermophilization). Species responses often lag behind climate warming, but the reasons for such lags remain largely unknown. Here, we analyzed multidecadal understory microclimate dynamics in European forests and show that thermophilization and the climatic lag in forest plant communities are primarily controlled by microclimate. Increasing tree canopy cover reduces warming rates inside forests, but loss of canopy cover leads to increased local heat that exacerbates the disequilibrium between community responses and climate change. Reciprocal effects between plants and microclimates are key to understanding the response of forest biodiversity and functioning to climate and land-use changes.
Keywords: stromy; Evropa; Europe; Microclimate; Trees; Global Warming; lesy; globální oteplování; mikroklima; Forests